Tumour-associated macrophages in human meningiomas - Rahmina Meta; Henrik Sahlin Pettersen; Sofie Eline Tollefsen; Borgny Ytterhus; Øyvind Olav Salvesen; Wenche Sjursen; Sverre Helge Torp (PLoS ONE, 2025)
Tumour-associated macrophages (TAMs) are regarded as potential therapeutic targets due to “pro-tumoral” and “anti-tumoral” phenotypes. Human meningiomas contain considerable number of TAMs, but their clinical impact is sparsely investigated in these tumours. The aim of this study was therefore to investigate the presence, morphology, and distribution of TAMs in human meningiomas, and relate these findings to histopathology, meningioma subtypes, World Health Organization (WHO) grade, risk of recurrence, and overall survival. In this study, 147 WHO grade 1 and 2 primary meningiomas prepared as tissue micro arrays were included. Standard immunohistochemistry, with the antibodies Iba1 as a pan-marker for “all TAMs”, iNOS for M1 and Arginase 1 for M2 TAMs, was performed to investigate their infiltration in the meningioma tissue. The immunostainings were scanned and analysed digitally. TAMs were found in most of the meningiomas with varying amount of ramified and amoeboid appearances. The quantity of total TAMs (Iba1-stained) was found to be significantly higher in the age group ≥ 60 years compared with the younger age group. M2 cell dominated over M1 cell quantity, and a higher quantity of M2 TAMs was found in skull-base compared with non-skull base tumours. Meningothelial subtypes had a higher quantity of M2 TAMs compared with transitional and atypical ones. Furthermore, the M1/M2-ratio was higher in meningiomas linked to the convexities compared with tumours in the basal. No relations between TAMs and histological WHO grade or prognosis (time to recurrence and overall survival) were found. TAMs were common in our series of meningiomas. However, their infiltration showed no clinicopathological significance. Due to their complex dynamic characteristics and shifting phenotypes, the investigation of these immune cells is demanding. Therefore, the TAMs’ definite role in human meningiomas in relation to clinicopathological parameters and prognosis need to be further investigated.